Measuring the causal effect of women’s schooling on contraceptive use in Nigeria - Ajefu, Joseph Boniface (Routledge, 2019)
This paper uses the 2008 Nigerian Demographic Health Survey to investigate the effect of women’s schooling on contraceptive use. In order to control for endogeneity of women’s schooling, this paper uses an instrumental variable approach, with the free primary education programme in Nigeria introduced from 1976 to 1981, as an instrument for women’s schooling. The paper finds that the education of women increases the probability of using contraceptives. Disaggregating the results between traditional and modern contraceptive use, the results show a positive and significant impact of women’s education on both modern and traditional contraceptive use. The findings of the study lend credence to the evidence that birth control measures can lead to better timing and spacing of births that allow women to significantly expand their economic opportunities and life prospects. These have implications for women’s economic empowerment and gender equality, which are vital for any sustainable development policy.
Development Southern Africa
Keywords: Female; schooling; causal; effect; contraceptives; Nigeria